Indonesian Local Community Livestock Deposit as A Step for Joint Benefits - Habibie, Samas Adimisa Mishbah (Future Science / FSH-PH Publications, 2022)
This study aims to determine the extent to which the level of benefit of local farmers and the community involved in investment (deposits) in the livestock sector. At the same time providing knowledge for the wider community to encourage them to participate in their money (Desposito) in cooperation for local livestock production. So that later it becomes the value of the common good and boosts the quality of local livestock products. The method used is qualitative phenomenology and literature review. The object of research is local cattle farmers who use a profit-sharing system and the cattle investors. Therefore, this research was conducted in the cattle village of Lalangon Village, Madura Island, Indonesia. The results of this study show that the profit sharing for local livestock, especially cattle, is very good for the livestock investors. For local farmers, it is helped by the existence of capital to buy cows to be reared. This collaboration will certainly help local farmers to earn income and also benefits for the community from the livestock investment. The general profit-sharing scheme is very positive in the nation's economic growth, including being able to create income fields for villagers who are still traditionally traditional and help meet the needs of national agricultural products such as meat needs.